Advanced Computing and Systems for Security Volume Eight - Chaki, Rituparna; Cortesi, Agostino; Saeed, Khalid; Chaki, Nabendu (Advances in Intelligent Systems and Computing, 2019)
The book includes extended versions of selected papers discussed and presented at the 5th International Doctoral Symposium on Applied Computation and Security Systems (ACSS 2018) held in Kolkata, India on February 9-11, 2018. The symposium was organized by the University of Calcutta's Department of Computer Science & Engineering and A. K. Choudhury School of Information Technology, and the International partners were Ca Foscari University of Venice, Italy and Bialystok University of Technology, Poland. Reflect the symposium's sessions, the book discusses topics such as biometrics, image processing, pattern recognition, algorithms, cloud computing, wireless sensor networks and security systems.